2021
DOI: 10.1088/1742-6596/1973/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Double Pass water passage in Evacuated Tube with Parabolic Trough Collector

Abstract: In this paper, a new design, fabricate and investigate the performance of the parabolic trough systems (PTC) by using double pass water passage in evacuated tube technology. This system can be used for heating water in winter season without assistive devices. The double-pass method utilizing to improve thermal performance for PTC by increasing the path of water flow in the evacuated tube and then increase the rate of the outlet temperature. Besides, the evacuated tube was used to decrease the thermal losses, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This approach does not need assistance equipment to heat water in the cold. The doublepass technique increases PTC's thermal performance by increasing the pace at which water exits the evacuated tube and broadening the flow channel [22]. Employing an evacuated tube to prevent heat loss made it feasible to increase thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This approach does not need assistance equipment to heat water in the cold. The doublepass technique increases PTC's thermal performance by increasing the pace at which water exits the evacuated tube and broadening the flow channel [22]. Employing an evacuated tube to prevent heat loss made it feasible to increase thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that thermal efficiency with using porous media was greater than this without using it. Double waterway in vacuum tube technology has been used in new design, fabrication and performance inspection of parabolic trough by Bassem et al [9]. This system can be used to raise the temperature of water in the winter without auxiliary devices.…”
Section: Introductionmentioning
confidence: 99%